2017
DOI: 10.1124/jpet.116.239228
|View full text |Cite|
|
Sign up to set email alerts
|

Antidepressant Potential of (R)-Ketamine in Rodent Models: Comparison with (S)-Ketamine

Abstract: The rapid-acting and long-lasting antidepressant effects of ()-ketamine have recently gained much attention. Although ()-ketamine has been studied as an active isomer, recent evidence suggests that ()-ketamine exhibits longer-lasting antidepressant effects than ()-ketamine in rodents. However, the antidepressant potential of ()-ketamine has not been fully addressed. In the present study, we compared the antidepressant effects of ()-ketamine with those of ()-ketamine in animal models of depression, including a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
152
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(172 citation statements)
references
References 33 publications
14
152
5
1
Order By: Relevance
“…( S )-ketamine has ~4-fold greater affinity/potency at inhibiting the NMDAR compared to its ( R )-ketamine enantiomer 13, 111ā€“115 . Hashimoto and colleagues were the first to report superior and longer-lasting antidepressant actions of ( R )-ketamine compared with ( S )-ketamine in rodent models 116ā€“118 . These findings were subsequently replicated by Zanos et al .…”
Section: Nmdar Inhibition-independent Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…( S )-ketamine has ~4-fold greater affinity/potency at inhibiting the NMDAR compared to its ( R )-ketamine enantiomer 13, 111ā€“115 . Hashimoto and colleagues were the first to report superior and longer-lasting antidepressant actions of ( R )-ketamine compared with ( S )-ketamine in rodent models 116ā€“118 . These findings were subsequently replicated by Zanos et al .…”
Section: Nmdar Inhibition-independent Mechanismsmentioning
confidence: 99%
“…(2016), who showed that ( S )-ketamineā€™s antidepressant behavioral actions require higher doses compared to those of ( R )-ketamine 13 . The superiority of ( R )-ketamine does not seem to be related to a U-shaped dose response of the drugs, as it has been shown superior to ( S )-ketamine with up to a 30-fold range of doses in multiple mouse tests of antidepressant efficacy 13, 118 . Importantly, administration of equal, antidepressant-relevant, doses of ( R )- and ( S )-ketamine in mice did not yield different levels of these enantiomers in the brain of mice 13 , indicating that the antidepressant superiority of ( R )-ketamine in rodent models is not due to greater brain exposure.…”
Section: Nmdar Inhibition-independent Mechanismsmentioning
confidence: 99%
“…Moreover, ( S )-ketamine decreased escape failures in the learned helplessness paradigm [45] and reduced high behavioral despair in the forced-swim test following repeated corticosterone administration [65] in rodents. These behavioral actions of ( S )-ketamine in rodent tests require higher doses compared to the ( R )-ketamine enantiomer [45, 64, 65], indicating that ( R )-ketamine is a more potent antidepressant compared to the ( S )-ketamine enantiomer, at least in rodents [66]. The ( S )-ketamine enantiomer is currently in Phase III clinical trials for the treatment of treatment-resistant depression and suicidal ideation after receiving the FDA Fast Track Designation (Clinical Trial ID: NCT02417064).…”
Section: Ketamine: the Prototype Rapid-acting Antidepressantmentioning
confidence: 99%
“…For example, ( R )-ketamine has a ~4-fold lower affinity/potency for blocking the NMDAR compared to ( S )-ketamine, but is a more potent antidepressant than ( S )-ketamine in the 24-h forced-swim test, the learned helplessness and novelty-suppressed feeding tests, as well as in reversing anhedonia following chronic social defeats in rodents [45, 64, 65, 99, 100]. …”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…Subsequent studies have confirmed superiority of ( R )-ketamine over ( S )-ketamine in rodent antidepressant-relevant behavioral outcomes using up to a 30-fold range of doses (4, 5). Notably, the difference in antidepressant potency is not due to bioavailability differences since administration of equal doses of these enantiomers does not yield different drug concentrations in the brains of rodents (4, 5). Given that ( S )-ketamine is a stronger inhibitor of the NMDAR, yet ( R )-ketamine is a more potent antidepressant, these preclinical findings indicate it is unlikely ketamine exerts its antidepressant actions merely via inhibition of the NMDAR.…”
mentioning
confidence: 94%